FORMULASI KATALIS BIFUNGSIONAL SINTESA DME SATU TAHAP - Ade Syafrinaldy; Zulaicha Dwi Hastuti (Jurnal Energi dan Lingkungan (Enerlink), 2017)
This research is aiming to formulate the most appropriate catalyst which is expected to be able to directthe reaction to form Dimethyl Ether (DME) in direct synthesis process using dual catalyst. It iscommonly known that DME can be formulated from synthetic gasses reaction, H2 and CO. Theprocess might be gone through indirect synthesis, methanol synthesis and dehydration, or directsynthesis in which both rections take place in one reactor. Both processes, indirect or direct synthesis,each would be needed the right catalyst. Dual catalyst is prepared by mixing physically methanolsynthesis catalyst and methanol dehydration to form DME.As methanol dehydration catalyst, we makeuse of HZSM-5 with Si/Al ratio of 25 and 90. This HZSM-5 is firstly calcined for 6 hours at 500°C. Thetemperature is raised to 500°C from ambient with pace of 5°C/min. The methanol synthesis catalyst isbased on CuZnAl, made by copresipitation method from Cu(NO3)2.3H2O; Zn(NO3)2.4H2O andAl(NO3)2.9H2O. The catalyst was then calcined at 350 ° C for 6 hours, then reduced by hydrogen 10 ml /minute and nitrogen 90 ml / min at 240 ° C, atmospheric pressure for 10 hours to remove the Ocomponent in the catalyst. The catalyst that has been prepared is CuZnAl with a ratio of 4: 3: 1; 5: 3: 1and 6: 3: 1. The ratio of the two catalysts is 2: 1 for Cu / Zn / Al2O3: HZSM-5. The catalytic activity test iscarried out using a continuous tubular fixed-bed microactivity reactor. The reaction is carried out at apressure between 3 - 4 MPa and a temperature in the range of 200 - 300 ° C. T The flow rate of thereactant gas is controlled by a mass flow controller, with a mass of 1 g of catalyst. Through the catalyticactivity test, the best methanol synthesis was given by CuZnAl catalyst with a 5: 3: 1 molar ratio, whichresulted in a CO conversion of 19.66% greater than the commercial catalyst of CZA-Sudchemie of15.62%. As for dehydration of methanol, the best result was given by Sudchemie-ZSM-5 catalyst withSi /Al 25 ratio resulting in higher DME concentration (0.90%) than Si /Al 90 ratio (0.45%).Keywords : direct synthesis, methanol synthesis, methanol dehydration, dual catalyst, CO conversion